The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1136/sextrans-2017-053178
|View full text |Cite
|
Sign up to set email alerts
|

Characterising HIV transmission risk among US patients with HIV in care: a cross-sectional study of sexual risk behaviour among individuals with viral load above 1500 copies/mL

Abstract: Objectives Viral load and sexual risk behaviour contribute to HIV transmission risk. High HIV viral loads present greater transmission risk than transient viral “blips” above an undetectable level. This paper therefore characterises sexual risk behaviour among HIV patients in care with viral loads >1500 copies/ml and associated demographic characteristics. Methods This cross-sectional study was conducted at six HIV outpatient clinics in the United States. The study sample comprises 1315 HIV patients with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
6
0
4
Order By: Relevance
“…Incomplete virological suppression is commonly due to irregular drug intake and/or antiretroviral drug resistance [3,4]. This compromises treatment outcomes for the individual, and also entails a risk of onward transmission, including dissemination of drugresistant strains [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete virological suppression is commonly due to irregular drug intake and/or antiretroviral drug resistance [3,4]. This compromises treatment outcomes for the individual, and also entails a risk of onward transmission, including dissemination of drugresistant strains [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…One potential explanation for higher HIV seroconcordance among HIV‐positive heterosexual couples is that individuals living with HIV may have intentionally chosen partners with the same HIV status. In high‐income settings, several quantitative and qualitative studies have reported that MSM choose seroconcordant partners to reduce the risk of HIV acquisition and transmission , and more likely to do so than heterosexual men and women . Evidence from heterosexual couples in SSA suggests that individuals living with HIV may seek and receive more social support from seroconcordant partners .…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, virally suppressed was categorized as an HIV viral load <200 copies/mL rather than <1,500 copies/mL, which research indicates is the threshold of HIV-RNA needed to sexually transmit HIV. [4547] This categorization may have resulted in fewer individuals being classified as suppressed than the less conservative measures would assume. Supplemental analyses conducted to mirror analytics presented in Tables 1 and 3 (Table A in S1 File, and Table B in S1 File) show the results did not significantly differ when increasing the viral load cutoff from <200 copies/mL to <1,500 copies/mL.…”
Section: Discussionmentioning
confidence: 99%